2012
DOI: 10.1029/2011jd016854
|View full text |Cite
|
Sign up to set email alerts
|

An annual cycle of size‐resolved aerosol hygroscopicity at a forested site in Colorado

Abstract: [1] The ability of particles composed wholly or partially of biogenic secondary organic compounds to serve as cloud condensation nuclei (CCN) is a key characteristic that helps to define their roles in linking biogeochemical and water cycles. In this paper, we describe size-resolved (14-350 nm) CCN measurements from the Manitou Experimental Forest in Colorado, where particle compositions were expected to have a large biogenic component. These measurements were conducted for 1 year as part of the Bio-hydro-atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
70
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 83 publications
(105 reference statements)
20
70
1
1
Order By: Relevance
“…The simulated growth of particles above 15 nm compares well with the DMPS measurements. These simulations are also consistent with results from Levin et al (2012Levin et al ( , 2014 for hygroscopicity measurements at the BEACHON-ROCS site; these authors showed that growth of new particles was likely driven by biogenic secondary organic species, and the NPF events ultimately impacted aerosol chemical and physical properties for particles up to cloud condensation nuclei (CCN) sizes. Since lump sums of different oxidation products were used as the condensing vapors in this modeling study, it was not possible to assign exact physical properties to the vapors.…”
Section: Aerosol Simulationssupporting
confidence: 76%
“…The simulated growth of particles above 15 nm compares well with the DMPS measurements. These simulations are also consistent with results from Levin et al (2012Levin et al ( , 2014 for hygroscopicity measurements at the BEACHON-ROCS site; these authors showed that growth of new particles was likely driven by biogenic secondary organic species, and the NPF events ultimately impacted aerosol chemical and physical properties for particles up to cloud condensation nuclei (CCN) sizes. Since lump sums of different oxidation products were used as the condensing vapors in this modeling study, it was not possible to assign exact physical properties to the vapors.…”
Section: Aerosol Simulationssupporting
confidence: 76%
“…In contrast, the newly formed particles consisted of a minor fraction of water-soluble fraction (16 %) in Hyytiälä, Finland (Ehn et al, 2007). Other observations in the clean atmospheric environments (relative to Beijing), such as a forested site in Colorado (Levin et al, 2012), Mace Head, Ireland (Väkevä et al, 2002), and Melpitz, Germany , also showed that low water-soluble compounds, most likely secondary organic species, mainly contributed to new particle growth. Differently, in the urban area of Atlanta (Sakurai et al, 2005), the water-soluble fraction dominated in the newly formed particles, which was similar to our observation in this study.…”
Section: Case Study: Particle Hygroscopicity During An Npf Eventmentioning
confidence: 92%
“…A similar size dependency of particle hygroscopicity was observed in various environments. For examples, Levin et al (2012Levin et al ( , 2014 and Paramonov et al (2013) reported that particle hygroscopicity increased with particle size at a forested site in Colorado and a boreal environment of southern Finland at the SMEAR station, respectively. Jurányi et al (2013) observed that particle hygroscopic growth increased with increasing dry diameter in the urban areas of Paris.…”
Section: Overview Of Particle Hygroscopic Growth and The Mixing Statementioning
confidence: 99%
See 1 more Smart Citation
“…By combining this information with the observed values of κ between about 0.1 and 0.45 for sub-100 nm particles originating from nucleation (e.g. Dusek et al, 2010;Cerully et al, 2011;Sihto et al, 2011;Levin et al, 2012), we end up with threshold diameters larger than about 70-80 nm in boundary-layer clouds (Fig. 1).…”
Section: Experimental Findingsmentioning
confidence: 99%